An improved procedure for isolating adult mouse cardiomyocytes for epicardial activation mapping. Issue 24 (10th November 2021) - Zhang, Ziguan; Zheng, Wuyang; He, Dehua; Hu, Zichao; Xie, Qiang; Huang, Meirong; Li, Weihua; Huang, Zhengrong
Abstract: Cardiovascular disease is a leading cause of death and disability worldwide. Although genetically modified mouse models offer great potential for robust research in vivo, in vitro studies using isolated cardiomyocytes also provide an important approach for investigating the mechanisms underlying cardiovascular disease pathogenesis and drug actions. Currently, isolation of mouse adult cardiomyocytes often relies on aortic retrograde intubation under a stereoscopic microscope, which poses considerable technical barriers and requires extensive training. Although a simplified, Langendorff‐free method has been used to isolate viable cardiomyocytes from the adult mouse heart, the system requires enzymatic digestions and continuous manual technical operation. This study established an optimized approach that allows isolation of adult mouse cardiomyocytes and epicardial activation mapping of mouse hearts using a Langendorff device. We used retrograde puncture through the abdominal aorta in vivo and enzymatic digestion on the Langendorff perfusion device to isolate adult mouse cardiomyocytes without using a microscope. The yields of isolated cardiomyocytes were amenable to patch clamp techniques. Furthermore, this approach allowed epicardial activation mapping. We used a novel, simplified method to isolate viable cardiomyocytes from adult mouse hearts and to map epicardial activation. This novel approach could be beneficial in more extensive research in the cardiac field.